А я тебя нашел! - Grishin, Lev; Antonicheva, Marta (Russia, 2012)
A short film about the levity of human life. An elderly Russian woman tells the story her late husband and their life together. She begins with their childhood, when they first met, and concludes the story with the most important day of all - the wedding.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films